A survey of roof failures in Oyo State of Nigeria (2007)
Rising incidences of roof failures in recent times in many parts of Oyo state, Nigeria have become a matter of concern and a survey was undertaken to investigate the pattern of failure, causative agents, consequences and possible remedial measures aimed at curtailing these occurrences. The survey adopted the use of questionnaires, interview schedules and focus group discussions. Information considered of relevance to the study was the type of roof, materials used for construction, type of buildings and topography of the environment. Besides being blown off, which is the popularly acknowledged index of failure, a number of roofs were found to have failed in their primary function of offering protection against rain and reduced solar radiation even when they were not blown off. Wind is a major causative agent of roof failures as it either completely removes the roof or tears it, leading to leakages. Corrosion was also a major factor resulting in leakages. The consequences of roof failures include damage to personal belongings and exposure of inhabitants and livestock to inclement weather conditions, and in some cases livestock were lost. Added to these are the psychological trauma to which victims are subjected and progress retardation as in many cases, no meaningful family projects can be executed while waiting for the roof to be replaced. As panacea, the adoption of a good maintenance culture, good workmanship and consultation of experts in the selection and construction of roofs are recommended.